Analyzing Elementary School Students’ Geometry Comprehension Based on Van Hiel’s Theory - Chairil Faif (Penerbit STKIP PGRI Bangkalan, 2026)
Teaching geometry in elementary school sets out to build and develop students’ logical thinking skills. Comprehension of geometry topics is expected to develop the students’ skills to solve everyday problems. However, this learning objective has not been met as expected. In Indonesia, there are many elementary school students who still do not understand the basic concepts of geometry, such as shapes and planes. Based on this problem, the researcher conducted a study to examine students’ comprehension of geometric concepts. This study is of an experimental kind and involves two classes: an experimental class and a control class. To solve the problem of learning geometric topics, the researcher utilizes Van Hiel’s theory. Geometry learning in the first class is delivered using a learning approach based on the Van-Hielé theory (experimental group), while learning in the second class is delivered with the conventional approach (control group). This study comprised 150 students, drawn from primary five, representing two classifications of medium and low performance from the selected schools found in Banjarmasin. Before conducting the study, the researcher designed a learning scenario and research procedure to ensure the study went as expected. This study concludes that students’ comprehension of geometric concepts after Van-Hielé’s Theory-Based Geometry Learning belongs to the medium category, which is better than the students’ comprehension of geometric concepts after conventional learning, which is in the low category. Conclusively, Van Hiel’s geometry learning theory is found to be effective in teaching and learning mathematics.